Small wind turbines for electricity and irrigation : design and construction - Rosato, Mario Alejandro; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
This practical book deals with the technology of small-power wind turbines as opposed to widely diffused industrial wind turbines and wind farms. It covers the most common wind turbine technologies in the small power segment: horizontal axis both for electrical generation and water pumping, vertical axis of the Darrieus type, and vertical axis of the Savonius type. With each chapter following the same didactic scheme a theoretical explanation and practical examples showing calculation procedures it allows anybody with basic technical knowledge to design and build a small wind turbine for any site. A set of simple spreadsheets is available for download, each providing further examples of how to solve specific design problems and allowing the reader to play with changing parameters and see what-if. This simple trial-and-error learning process allows beginners to develop the feeling of the orders of magnitude involved in the design of a small wind power system, its potential advantages on other alternative solutions, and its limitations under some special circumstances.
chapter 1 Small Wind Turbines: A Technology for Energy Independence and Sustainable Agriculture -- chapter 2 General Theory of Wind-Driven Machines -- chapter 3 Simplified Aerodynamic Theory for the Design of the Rotor s Blades -- chapter 4 Practical Design of Horizontal Axis Wind Turbines -- chapter 5 Practical Design of Aerodynamic Action Vertical Axis Wind Turbines -- chapter 6 Practical Design of Savonius Turbines and Derived Models -- chapter 7 Engineering of the Support Structures for Wind Turbines -- chapter 8 Probability Distribution of the Wind Speed and Preliminary Design of Wind Power Installations -- chapter 9 Sizing Energy Storage Systems -- chapter 10 Design of Wind Pumping Systems -- chapter 11 Unconventional Wind-Driven Machines -- chapter 12 Aerodynamic Characteristics of Blunt Bodies and Airfoils.
Keywords: TECHNOLOGY & ENGINEERING / Chemical & Biochemical; TECHNOLOGY & ENGINEERING / Power Resources / Alternative & Renewable; Wind turbines -- Design and construction